2012
DOI: 10.2319/101011-633.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gradually induced backward movement of the mandible by a Twin Inclined Plane Device in rats

Abstract: Objective: To develop a model of gradually induced backward movement of the mandible under normal masticatory action and to examine morphological changes in the mandible and condylar cartilage in rats. Materials and Methods: The newly developed Twin Inclined Plane Device (TIPD) was composed of upper and lower posterior metal crowns with a long inclined plane on both sides separately and was applied in experimental groups of 6-week-old male Wister rats. After 3, 14, 30, and 60 days, the rats were euthanatized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Asano appears to have faced the same challenge in highlighting similar landmarks [ 57 ]. Such developmental restriction is in agreement with the observations of Desai et al [ 62 ] and Cholasueksa et al [ 8 ], and the conclusions of Asano [ 57 ], Farias-Neto et al [ 81 ], and Hua et al [ 82 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Asano appears to have faced the same challenge in highlighting similar landmarks [ 57 ]. Such developmental restriction is in agreement with the observations of Desai et al [ 62 ] and Cholasueksa et al [ 8 ], and the conclusions of Asano [ 57 ], Farias-Neto et al [ 81 ], and Hua et al [ 82 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was introduced by Desai et al [ 62 ], although their research did not report many details on osseous mandibular change, but focused mainly on the temporomandibular joint. It was adopted by Cholasueksa et al [ 8 ] and Farias-Neto et al [ 81 ], whereas Hua et al [ 82 ] and Wang et al [ 59 ] used modified upper/lower devices, unlike Asano [ 57 ], Tsolakis [ 15 ] and Teramoto et al [ 10 ], who selected extra-oral appliances. Teramoto et al mention that the magnitude of the traction was excessive, and thus ended up traumatic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal component of the chewing force, F s, is transmitted to the posterior region of the condyle (Figure 1(a)). Therefore, the posterior region was determined as the focus of the present study [14]. The expression of VEGF (Figure 2(c)), type II collagen (Figure 2(d)), and osteoclasts (Figure 2(e)) was semiquantified using an Olympus DP72 microscope (Olympus DP72 microscope, Olympus Corporation, Japan) and the Image-pro plus 6.0 software (Media Cybernetics, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was found that the posterior margin of the condyle was significantly flattened after the TIPD treatment. It was speculated that TIPD can cause persistent remolding in the posterior region of the condylar cartilage [14]. However, the condylar changes in rats, which trigger the mechanism, remain unclear.…”
Section: Introductionmentioning
confidence: 99%